The Natural Antiangiogenic Compound AD0157 Induces Caspase-Dependent Apoptosis in Human Myeloid Leukemia Cells - García-Caballero, Melissa; Martínez-Poveda, Beatríz; Medina, Miguel A.; Quesada, Ana R. (Frontiers in Pharmacology, 2017)
Evasion of apoptosis is a hallmark of cancer especially relevant in the development and the appearance of leukemia drug resistance mechanisms. The development of new drugs that could trigger apoptosis in aggressive hematological malignancies, such as AML and CML, may be considered a promising antileukemic strategy. AD0157, a natural marine pyrrolidinedione, has already been described as a compound that inhibits angiogenesis by induction of apoptosis in endothelial cells. The crucial role played by defects in the apoptosis pathways in the pathogenesis, progression and response to conventional therapies of several forms of leukemia, moved us to analyze the effect of this compound on the growth and death of leukemia cells. In this work, human myeloid leukemia cells (HL60, U937 and KU812F) were treated with AD0157 ranging from 1 to 10 μM and an experimental battery was applied to evaluate its apoptogenic potential. We report here that AD0157 was highly effective to inhibit cell growth by promotion of apoptosis in human myeloid leukemia cells, and provide evidence of its mechanisms of action. The apoptogenic activity of AD0157 on leukemia cells was verified by an increased chromatin condensation and DNA fragmentation, and confirmed by an augmentation in the apoptotic subG1 population, translocation of the membrane phosphatidylserine from the inner face of the plasma membrane to the cell surface and by cleavage of the apoptosis substrates PARP and lamin-A. In addition, AD0157 in the low micromolar range significantly enhanced the activities of the initiator caspases-8 and -9, and the effector caspases-3/-7 in a dose-dependent manner. Results presented here throw light on the apoptogenic mechanism of action of AD0157, mediated through caspase-dependent cascades, with an especially relevant role played by mitochondria. Altogether, these results suggest the therapeutic potential of this compound for the treatment of human myeloid leukemia.